Identification of Antibody Against SNRPB, Small Nuclear Ribonucleoprotein-Associated Proteins B and B', as an Autoantibody Marker in Crohn's Disease using an Immunoproteomics Approach. (14th February 2017) - Wang, Haoyu; Demirkan, Gokhan; Bian, Xiaofang; Wallstrom, Garrick; Barker, Kristi; Karthikeyan, Kailash; Tang, Yanyang; Pasha, Shabana F.; Leighton, Jonathan A.; Qiu, Ji; LaBaer, Joshua
Abstract: Background: Current non-invasive biomarkers for Crohn's disease are limited in their utility. Progress in identifying individual autoantigens and autoantibodies in Crohn's disease has been challenging due to limitations of available immunoassays. Aims: Our aim was to identify autoantibodies associated with Crohn's disease that may be useful in diagnosis and management using an innovative protein array technology, namely nucleic acid programmable protein arrays [NAPPA]. Methods: Serum samples of 96 patients with established Crohn's disease and 96 healthy controls were included and evenly split into discovery and validation sets randomly. Autoantibodies of both IgG and IgA classes were profiled against ~1900 human proteins in the discovery set on NAPPA. Autoantibodies discovered to be Crohn's disease-specific were further validated in the independent validation set by enzyme-linked immunosorbent assay. Results: Overall, reactivity of IgG autoantibodies was stronger than that of IgA autoantibodies; however, IgA autoantibodies showed greater differential reactivity between cases and controls. Four IgA autoantibodies against SNRPB, PRPH, PTTG1 and SNAI1 were newly identified with sensitivities above 15% at 95% specificity, among which anti-SNRPB-IgA had the highest sensitivity of 24.0%. Autoantibodies associated with specific disease subtypes were also found. Conclusions: As one of the first studies to use immunoproteomics for the identification of autoantibodies in Crohn's disease, our results support the utility of NAPPA in implementing future expanded studies with better coverage of the human proteome and microbial proteomes relevant to Crohn's disease and identifying antibody markers that may have clinical impact in diagnosis and management.